THE EFFECT OF HEAVY METALS ON THE MORPHOLOGY OF EICHHORNIA CRASSIPES-MART. SOLMS. IN PANTEKA STREAM. - CORNELIUS TOCHUKWU, NWANKWO; MOLTONG YILWA, VICTORIA; MATTHEW CHIKA, EMERE; BENJAMIN CHIKWENDU, ONUSIRIUKA; MAGAJI, YAKUBU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Heavy metals are indispensable for normal plant growth and development. This study was conducted to examine heavy metals impact on the morphology of Eichhornia crassipes. Morphological parameters of the plant were studied. Water samples were collected from Panteka stream where mechanic and farming activities are carried out. The stream was divided into three points (A, B and C) and pond water, where farming is predominant served as the control site (D). Heavy metals were analyzed during dry and wet seasons for the presence of cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn). The result obtained revealed that the highest mean plant height (80.86cm), root length (41.40cm), leaf length (17.68cm), leaf number (21.20), leaf width (14.64cm) and flower number (3) were observed at sampling points A, D, C, B and A respectively. Among the heavy metals analyzed Cd had the highest concentration (0.78mg/kg). Cadmium and Lead were above, while the others were below the standards of FEPA and USEPA. The roots and leaves of E. crassipes showed clear signs of abscission and elongated roots at the control sites. The Pearson correlation coefficient between heavy metals at sampling points during the two seasons revealed a significant difference.